Advanced Foreign Technologies as a Means of Increasing Efficiency in Classroom and Extracurricular Language Classes (Texas Journal of Medical Science, 2023)
in the article, the implementation of educational content focused on personal development, the need to introduce advanced technologies into the educational process requires ensuring a balance between educational content and its purpose.